The Economics of the Iron and Steel Industry (Book). - Lang, Theodore (The Accounting Review, 1937)
Reviews the book "The Economics of the Iron and Steel Industry," by Carroll R. Daugherty, Melvin G. de Chaeran and Samuel S. Stratton.